2015
DOI: 10.1161/jaha.115.001862
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Validation of RNF213 Coding Variants in Japanese Patients With Moyamoya Disease

Abstract: BackgroundA founder variant of RNF213, p.R4810K (c.14429G>A, rs112735431), was recently identified as a major genetic risk factor for moyamoya disease (MMD) in Japan. Although the association of p.R4810K was reported to be highly significant and reproducible, the disease susceptibility of other RNF213 variants remains largely unknown. In the present study, we systematically evaluated the coding variants detected in Japanese patients and controls for associations with MMD.Methods and ResultsTo detect variants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 33 publications
6
45
1
3
Order By: Relevance
“…Interestingly, the patients with the homozygous p. R4810K variant were stable without increased likelihood of recurrent stroke after revascularization. According to our data, it is difficult to predict prognosis after revascularization using the p.R4810K founder variant as a prognostic biomarker, though the homozygous founder variant may influence some aspects of the disease, such as the age of onset, as suggested by prior reports [6,7].…”
Section: Relationship Between the Rnf213 Genotype And Long-term Clinimentioning
confidence: 76%
See 3 more Smart Citations
“…Interestingly, the patients with the homozygous p. R4810K variant were stable without increased likelihood of recurrent stroke after revascularization. According to our data, it is difficult to predict prognosis after revascularization using the p.R4810K founder variant as a prognostic biomarker, though the homozygous founder variant may influence some aspects of the disease, such as the age of onset, as suggested by prior reports [6,7].…”
Section: Relationship Between the Rnf213 Genotype And Long-term Clinimentioning
confidence: 76%
“…Several studies confirmed that homozygosity of this RNF213 founder variant influenced the severity of the clinical disease phenotype [6][7][8]. A previous Japanese study showed that its homozygosity was significantly associated with early-onset MMD and cerebral infarction at diagnosis [7].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Of interest, homozygosity for the R4810K variant leads to MMD with extracranial systemic vasculopathy [165]. Given that around 80 % of Japanese MMD patients harbor susceptibility variants of RNF213 , 17q25.3 is considered a major disease locus [159, 161], however, the lack of a cerebrovascular phenotype in Rnf213 knockout mice and high prevalence of RNF213 variants in healthy control populations suggest multifactorial etiology [166]. On the other hand, autosomal-recessive MMD with achalasia has been associated with mutations in GUCY1A3 on chromosome 4q32.1 [167], encoding a subunit of the main receptor for nitric oxide (NO) [168].…”
Section: Hereditary Hemorrhagic Cerebrovascular Diseasementioning
confidence: 99%